2016
DOI: 10.1093/mutage/gew043
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles exhibit size-dependent differential toxicity and induce expression of syncytin-1 in FA-AML1 and MOLT-4 leukaemia cell lines

Abstract: Human endogenous retrovirus (HERV) sequences make up approximately 8% of the human genome and increased expression of some HERV proteins has been observed in various pathologies including leukaemia and multiple sclerosis (MS). However, little is known about the function of these HERV proteins or environmental factors which regulate their expression. Silver nanoparticles (AgNPs) are used very extensively as antimicrobials and antivirals in numerous consumer products although their effect on the expression of HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The mechanisms of HERV activation by viruses are relatively clear whereas those by physical and chemical factors remain uncertain (54,82,83). Hydroquinone (55), cupric ion (84), silver nanoparticles (85), and ultraviolet exposure (86), as well as hypoxia phenomenon (70) can influence the expression of HERVs in tumor cell lines. However, the underlying mechanism remains unknown ( Fig.…”
Section: Regulatory Mechanisms Of the Expression Of Hervs In Cancermentioning
confidence: 99%
“…The mechanisms of HERV activation by viruses are relatively clear whereas those by physical and chemical factors remain uncertain (54,82,83). Hydroquinone (55), cupric ion (84), silver nanoparticles (85), and ultraviolet exposure (86), as well as hypoxia phenomenon (70) can influence the expression of HERVs in tumor cell lines. However, the underlying mechanism remains unknown ( Fig.…”
Section: Regulatory Mechanisms Of the Expression Of Hervs In Cancermentioning
confidence: 99%
“…The published literature describes both upstream regulation of HERV expression as well as downstream effects of increased HERV activity [43,86]. Alqahtani et al found that cellular stress from contact with silver nanoparticles increases HERV-W Env protein expression through a possible survival response to an increase in reactive oxygen species (ROS) [86].…”
Section: Hematological Cancersmentioning
confidence: 99%
“…Blood cancers. The expression of HERVs has been reported in acute myeloid leukemia (AML) (12,(92)(93)(94), acute lymphoblastic leukemia (ALL) (12,93,94), acute mixed lineage leukemia (AMLL) (94), chronic myeloid leukemia (CML) (12), chronic lymphoblastic leukemia (CLL) (94), chronic mixed myeloid leukemia (CMML) (92), non-Hodgkin's lymphoma (NHL) and other lymphomas (94)(95)(96), essential thrombopenia (ET) (97), and myelodysplastic syndrome (MDS) (53) (Table II). The Np9 protein expressed by HERV-K activates a cascade of cellular signaling pathways (β-catenin, ERK, AKT, and Notch1), which helps in the proliferation of leukemia cells by increasing le1ukemia stem and progenitor cells (2,20).…”
Section: Expression Of Herv In Various Cancer Typesmentioning
confidence: 99%